INDUSTRIAL NOISE EFFECT ON HUMAN BODIES - Manoj kumar (International Journal of Research Science and Management, 2016)
The problem of noise in the industries around Saharanpur has been examined in this study; and noise measurement and survey studies have been carried out at concrete traverse, cement, iron and steel and textile factories located in this region. A questionnaire was completed by 256 workers during this study in order to determine the physical, physiological, and psychosocial impacts of the noise on humans and to specify what kind of measurements have been taken both by the employers and workers for protection from the effects of noise. It has been specified, during the surveys, that the noise levels detected in all the industries are much above the 80 dBA that is specified in the regulations: 74.83% of the workers in these industries are disturbed from the noise in their workplaces, 61.96% of them have complaints about their nervous situations, 32.96% of these workers are suffering hearing problems although they had not had any periodical hearing tests and they are not using ear protection equipment.